ANALISIS PENILAIAN SIKAP PADA PESERTA DIDIK DI KELAS IV PADA PROSES PEMBELAJARAN BERDASARKAN WAWANCARA WALIKELAS. - Nur Latifa Az-Zahara; Edhita Oktrifianty; Radita Maharani; Alicia Ivanna (STKIP Subang, 2026)
This study aims to analyze the implementation of attitude assessment for fourth-grade students in the learning process at elementary schools based on interviews with class teachers. The study employed a descriptive qualitative approach using a case study method, involving fourth-grade teachers as participants through semi-structured interviews and attitude assessment documentation. The results show that attitude assessment is conducted continuously through behavior observation, event recording, the use of rubrics and checklists, and intensive interaction between teachers and students. Consistent feedback and parental involvement also support the effectiveness of the assessment. The study identified challenges, such as limited time and a large number of students, which can be minimized through systematic and contextual assessment strategies. Thus, attitude assessment functions not only as an evaluation tool but also as an integral means of character development, supporting the social, emotional, and moral growth of students in accordance with the principles of the Merdeka Curriculum.